Modelling of equivalent mass and rigidity of continual segment of the inter-resonance vibration machine - Kachur, Oleksandr Y.; Lanets, Oleksij V.; Dmytriv, V.T.; Derevenko, Iryna A.; Horodetskyy, Ivan; Novitskyi, Yu. Ya. (Zielona Góra: Uniwersytet Zielonogórski)
The article deals with a continual segment of an inter-resonance vibration machine. In the form of a solid with distributed parameters this segment combines two defining parameters, namely: the inertial parameter of reactive: masses and appropriate rigidity of elastic coupling.
Keywords: three-mass vibration system; Rayleigh-Ritz method; continual segment; equivalent mass; equivalent rigidity